Seasonal variation of microalgae in relation to physico-chemical parameters of coastline of Kerala, India. - ARAVINDH. S; P. RUBAN (International Journal of Pharma and Bio Sciences, 2019)
Physico-chemical parameters study of Marine ecosystem is necessary because hydrochemistry affects its biota to a great extent. Quality of water influences the existence and growth of aquatic organisms. Hence, in the present investigation, some physico-chemical parameters studies were made on Coastline of Kerala such as Munnakal beach, Cherai beach, Ambedkhar beach, Aniyal beach and Kuzhupilly beach, Kerala, India and seasonal changes in the growth and distribution of microalgae along with phyico-chemical parameters were investigated for a period of one year from July 2017 to May 2018. Sea Water samples were analysed for parameters like pH, turbidity, conductivity, dissolved oxygen, BOD, COD, bicarbonate, dissolved solids, nitrate, ammonia, phosphate, fluoride and their average value was 8.107, 21.99NTU, 50.769mS/cm, 7.577mg/lit, 5.373mg/lit, 505.1mg/lit, 165.75mg/lit, 866.75mg/lit, 0.602mg/lit, 0.036mg/lit, 0.103mg/lit, and 1.344mg/lit respectively. Investigation on diversity of microalgae flora was made and data revealed that Coastline of kerala, the dominant members belonged to Cyanophyceae (82 genera) followed by Bacillariophyceae (28 genera), and Chlorophyceae (16 genera). Among the five beaches, munnakal beach was found to be rich in microalgae diversity and also their physico - chemical parameters are slightly different from others. The abundance of various algal groups on these beaches were in the percentage - Cyanophyceae 67.05%, Bacillariophyceae 22.22% and Chlorophyceae 12.69%, in one year study. Interrelationship between environmental, physico-chemical parameters and phytoplankton (Pearson’s Correlation matrix) was also studied. The significant (P< 0.0005) variation among seasons as well as a high influence of these parameters was observed on phytoplankton productivity Cyanophyceae, Bacillariophyceae, and chlorophyceae members showed significant positive correlation with nitrate, phosphorous and ammonia.